Enabling Sustainable Energy Transitions Practices of legitimation and accountable governance - Sareen, Siddharth (Springer Nature, 2020)
This open access book reframes sustainable energy transitions as being a matter of resolving accountability crises. It demonstrates how the empirical study of several practices of legitimation can analytically deconstruct energy transitions, and presents a typology of these practices to help determine whether energy transitions contribute to sustainability. The real-world challenge of climate change requires sustainable energy transitions. This presents a crisis of accountability legitimated through situated practices in a wide range of cases including: solar energy transitions in Portugal, urban energy transitions in Germany, forestland conflicts in Indonesia, urban carbon emission targets in Norway, transport electrification in the Nordic region, and biodiversity conservation and energy extraction in the USA. By synthesising these cases, chapters identify various dimensions wherein practices of legitimation construct specific accountability relations. This book deftly illustrates the value of an analytical approach focused on accountable governance to enable sustainable energy transitions. It will be of great use to both academics and practitioners working in the field of energy transitions.